Lesotho : Ex Post Assessment of Longer-Term Program Engagement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper presents Ex Post Assessment of Longer-Term Program Engagement for Lesotho. The paper reviews the experience of the IMF's engagement in Lesotho during the period 1991-2004, and briefly presents economic developments prior to these arrangements. It reviews performance under IMF-supported programs and analyzes the main factors accounting for that performance. The paper draws lessons from these program experiences and considers the main challenges facing Lesotho. The role that the IMF can play in helping the authorities to meet those challenges is also examined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet